Acrylamide-targeting renal miR−21a−5p/Fibrotic and miR122-5p/ inflammatory signaling pathways and the role of a green approach for nano-zinc detected via in silico and in vivo approaches - Alqahtani, Leena S.; Alosaimi, Manal E.; Abdel-Rahman Mohamed, Amany; Abd-Elhakim, Yasmina M.; Khamis, Tarek; Noreldin, Ahmed E.; El-Far, Ali H.; Alotaibi, Badriyah S.; Hakami, Mohammed Ageeli; Dahran, Naief; Babteen, Nouf A. (Frontiers in Pharmacology, 2024)
Any disruption in renal function can have cascading effects on overall health. Understanding how a heat-born toxicant like acrylamide (ACR) affects kidney tissue is vital for realizing its broader implications for systemic health. This study investigated the ACR-induced renal damage mechanisms, particularly focusing on the regulating role of miR-21a-5p/fibrotic and miR-122-5p/inflammatory signaling pathways via targeting Timp-3 and TP53 proteins in an In silico preliminary study. Besides, renal function assessment, oxidative status, protein profile, and the expression of renal biomarkers (Timp-1, Keap-1, Kim-1, P53, TNF-α, Bax, and Caspase3) were assessed in a 60-day experiment. The examination was additionally extended to explore the potential protective effects of green-synthesized zinc oxide nanoparticles (ZNO-MONPs). A four-group experiment including control, ZNO-MONPs (10 mg/kg b.wt.), ACR (20 mg/kg b.wt.), and ZNO-MONPs+ACR was established encompassing biochemical, histological, and molecular levels. The study further investigated the protein-binding ability of ZNO and MONPs to inactivate caspase-3, Keap-1, Kim-1, and TNFRS-1A. Results indicated that ZNO-MONPs significantly reduced ACR-induced renal tissue damage as evidenced by increased serum creatinine, uric acid, albumin, and oxidative stress markers. ACR-induced oxidative stress, apoptosis, and inflammation are revealed by biochemical tests, gene expression, and the presence of apoptotic nuclei microscopically. Also, molecular docking revealed binding affinity between ACR-BCL-2 and glutathione-synthetase, elucidating the potential mechanisms through which ACR induces renal damage. Notably, ZNO-MONPs revealed a protective potential against ACR-induced damage. Zn levels in the renal tissues of ACR-exposed rats were significantly restored in those treated with ACR + ZNO-MONPs. In conclusion, this study establishes the efficacy of ZNO-MONPs in mitigating ACR-induced disturbances in renal tissue functions, oxidative stress, inflammation, and apoptosis. The findings shed light on the potential renoprotective activity of green-synthesized nanomaterials, offering insights into novel therapeutic approaches for countering ACR-induced renal damage.